Entre campos e saberes: uma jornada reveladora nas escolas do campo de Santa Maria (RS) segundo educadores e diretores - Sudati, Larissa Schlottfeldt (2024)
This study investigated the reality of Rural Education in Santa Maria, focusing on the perceptions of educators and directors from 10 rural schools. The methodological choice of a qualitative case study allowed for an in-depth understanding of the educational dynamics in rural areas. The results highlighted the importance of more experienced educators but also pointed out challenges, such as the lack of workforce renewal and the need for policies to attract young professionals. The correlation between academic background and knowledge of the Operational Guidelines for Rural Education indicated the need for adjustments in educators' training curricula to better address rural realities. The integration of local themes into the curriculum and active community participation were emphasized as relevant strategies. The analysis of strategies to address rural-urban migration underscored the complexity of these issues, with diverse responses from educators. The inclusion of community knowledge in the political-pedagogical project and partnerships with universities were identified as positive practices. Educators emphasized the importance of transportation in student participation, highlighting the need for continuous improvements in access and mobility conditions. The study concluded that Rural Education faces challenges but also demonstrated educational excellence, a diversity of pedagogical practices, and the importance of policies sensitive to rural specificities. The findings provide insights for the development of more effective and inclusive educational policies for rural schools in Santa Maria.